Improvements in Incontinence with Self-Management in Patients with Anorectal Malformations - Märzheuser, Stefanie; Karsten, Katharina; Rothe, Karin (European Journal of Pediatric Surgery, 2016)
There are limited data available in children with anorectal malformation (ARM) regarding the use of transanal colonic irrigation delivered with the Peristeen system (Coloplast Denmark A/S, Humlebaek, Denmark). To our knowledge no study has combined the element of controlled evacuation with self-management strategies. Our center began offering this management regimen 5 years ago to patients suffering from fecal incontinence. The aim of this study was to appraise the results of this approach in children from 4 to 18 years with incontinence and fecal soiling secondary to ARM.Material and Methods Bowel management was initiated with the help of hydrosonography to evaluate bowel motility and the volume of the enema. The Peristeen irrigation system was used. Anorectal irrigation was repeated every 24, 48, or 72 hours. A personal schedule was developed based on every patient's individual preferences. Irrigations were self-administered by the patient while sitting on the toilet. Patients were controlled for soiling, time needed for irrigation, time interval between irrigations 6 and 12 months after start of therapy, with further yearly follow-ups.Results A total of 40 patients aged between 4 and 18 years were evaluated. After 12 months of therapy, 32 patients were free of symptoms of soiling. Six patients were soiling occasionally. Two patients did not follow the therapeutic regime. The average time needed for irrigation was 35 minutes, with the lower limit of 12 minutes and the upper limit of 60 minutes, irrigations where done every 24 hours in 12 patients. Overall 25 patients irrigated twice every 48 and 72 hours to achieve a constant 7-day rhythm. One patient irrigated every 5 days. At follow-up after 2, 3, and 4 years success rates were stable.Conclusion We suggest that colonic irrigation should be combined with self-management strategies in children with ARM. Adherence to therapy can be enhanced with the use of an individualized irrigation schedule. The amount of time required for the irrigation can be significantly reduced. Therefore, when establishing colonic irrigation in children and adolescents a focus should be placed on time-saving measures and self-regulation.
Keywords: anorectal malformations; incontinence therapy; self-management